Design and simulation of hydro turbine bladed overlapping to generate electricity in river ucayali - Ramírez-Chumbe, Carlos A. (2019)
Clean and renewable energy, such as hydro, are essential to mitigate climate change and are essential to banish the thermoelectric power. It is regarded as the potential energy source. In the present study it was possible to design an optimal model that fits the reality of Ucayali, an experimental prototype was also built and the feasibility of operation of the turbine is determined in slow and flowing flow power generation. Tests with large and small blade is made in the Ucayali River with the respective dimensions were measured forces deep in river, computer parts, and the length forming a grid design to prevent excessive accumulation of masses of algae trunks, branches and other bulky waste. Calculations show that the blade angle does not vary evenly along the radius, and the contribution to power generation considering the angular speed of the turbine.